Essential oils of leaves and pseudo stems Alpinia malaccensis and antimicrobial activities. (April 2020) - Jusoh, Shariha; Sirat, Hasnah Mohd; Ahmad, Farediah; Basar, Norazah; Bakar, Mohd. Bakri; Jamil, Shajarahtunnur; Haron, Suzana
Abstract: The essential oils from the leaves, pseudo stems, rhizomes and fruits of Alpinia malaccensis, collected from conservation garden, UPM were isolated by hydro distillation. The collected oils were analysed by capillary GC and GC-MS. The leaf, pseudo stem, rhizome and fruit oils afforded 73 and 24 constituents, respectively. The most abundant components in the leaf oil were β -pinene (20.02%), 1, 8-cineol (16.49%), trans- caryophyllene (8.69%) and α-pinene (6.64%), while 1, 8-cineole (36.81%), β-pinene (13.95%), α-terpineol (6.85%), trans-caryophyllene (7.49%) and α-terpinolene (6.85%) were the main constituents in the pseudo stems oil. Antimicrobial assay revealed that all the essential oils showed moderate to weak inhibition against the tested microorganisms. The leaf oil was the most active and inhibited both S. aureus and E. coli with MIC values of 7.81 μg/mL and 15.6 μg/mL, respectively.